Sex Differences in Gray Matter Volume of the Right Anterior Hippocampus Explain Sex Differences in Three-Dimensional Mental Rotation - Wei, Wei; Chen, Chuansheng; Dong, Qi; Zhou, Xinlin (Frontiers in Human Neuroscience, 2016)
Behavioral studies have reported that males perform better than females in 3-dimensional (3D) mental rotation. Given the important role of the hippocampus in spatial processing, the present study investigated whether structural differences in the hippocampus could explain the sex difference in 3D mental rotation. Results showed that after controlling for brain size, males had a larger anterior hippocampus, whereas females had a larger posterior hippocampus. Gray matter volume of the right anterior hippocampus was significantly correlated with 3D mental rotation score. After controlling for gray matter volume of the right anterior hippocampus, sex difference in 3D mental rotation was no longer significant. These results suggest that the structural difference between males’ and females’ right anterior hippocampus was a neurobiological substrate for the sex difference in 3D mental rotation.